Thermal consequences of sintering the borosilicate matrix blue-green color release properties - Tung, Ha Thanh; Nguyen Thi, Dieu An (Bulletin of Electrical Engineering and Informatics, 2023)
Color transformation glass ceramics were produced of borosilicate matrix co-doped (SrBaSm)Si2O2N2:(Eu3+Ce3+) blue–green (B-G) (abbreviated as (SBS)SON:(EuCe) B-G) phosphors using a two-step co-sintering technique. The shift in illumination characteristics and drift of chromaticity coordinates (CIE) of (SBS)SON:(EuCe) (B-G) phosphors and hue transformation glass ceramics were investigated over a 600–800 ºC sintering thermal range. With rising sintering heat, the illuminated strength and inner quantum yield (QY) of (abbreviated as B-G) phosphors and glass ceramics reduced. Once the sintering heat was raised above 750 ºC, the phosphors and hue transformation glass ceramics showed nearly no high point among their luminescence photoluminescence (PL) and photoluminescence excitation (PLE) bands of color. B-G phosphors have low heating steadiness at more elevated temperatures, according to the findings. The glass matrix destructed the phosphors lattice layout and the Ce3+ in the phosphors was oxidized to Ce4+, resulting in a reduction in the luminous characteristics of the color transformation glass ceramics.